Is Low Dose Aspirin Reduced the Risk of Preeklampsia? - Kurrniati, Era; Murti, Bhisma; Pamungkasari, Eti Poncorini (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: The maternal mortality rate is the number of maternal deaths resulting from pregnancy, childbirth and postpartum processes, which is an indicator of women's health status. Efforts that can be made to accelerate the reduction in maternal mortality are by ensuring that every mother is able to access quality health services. Low-dose aspirin has been proven to be a safe and effective primary prevention of preeclampsia. This study aims to determine the effect of low dose aspirin on the incidence of preeclampsia. Subjects and Method: Cross sectional research was conducted at the Community Health Center, Blora, Central Java, Indonesia. A sample of 200 pregnant women was selected using random sampling. The dependent variable is preeclampsia. The independent variables are age, income, aspirin consumption, primigravida, multigravida and hypertension. Data were collected by questionnaire and analyzed by multiple logistic regression. Results: The results of logistic regression analysis in this study concluded that the risk of preeclampsia increased at age <20 years or ≥35 years (OR= 4.62; 95% CI= 1.89 to 11.28; p= 0.001), gravida 2-3 (OR= 3.03; CI 95 %= 1.01 to 9.05; p= 0.047), gravida ≥3 (OR= 4.41; 95% CI= 1.07 to 18.18; p= 0.040) and history of hypertension (OR= 2.41; 95% CI= 1.02 to 5.69; p= 0.005 ). The risk of preeclampsia decreased with income > IDR 2,000,000 (OR= 0.44; 95% CI= 0.22 to 0.87; p= 0.019) and administration of low-dose aspirin (OR= 0.13; 95% CI= 0.05 to 0.35; p <0.001). Conclusion: The risk of preeclampsia increases with age, gravida 2-3, gravida ≥3 and history of hypertension. The risk of preeclampsia decreases with high income and administration of low-dose aspirin.